Salivary α-Amylase of Stem Borer Hosts Determines Host Recognition and Acceptance for Oviposition by Cotesia spp. (Hymenoptera, Braconidae) - Gladys B. Bichang'a; Gladys B. Bichang'a; Jean-Luc Da Lage; Kevin Sambai; Simon Mule; Bruno Le Ru; Bruno Le Ru; Laure Kaiser; Gerald Juma; Esther N. Maina; Paul-André Calatayud; Paul-André Calatayud (Frontiers in Ecology and Evolution, 2018)
Foraging insect parasitoids use specific chemical cues to discriminate between host and non-host species. Several compounds have been identified in “host location and acceptance.” However, nothing is known about the molecular variations in these compounds that could account for host-range differences between parasitoid species. In a previous study, it was shown that during the host-finding process, contact between the braconid Cotesia flavipes and its host is crucial, and that α-amylase of oral secretions from the host plays a key role for host acceptance and oviposition by the parasitoid. The present study sought to establish whether the variations in this enzyme could explain specific host recognition in different host-parasitoid associations. Different species and populations of the C. flavipes complex specialized on graminaceous lepidopteran stemborers were used. Electrophoresis of α-amylase revealed different isoforms that mediate the parasitoid's oviposition acceptance and preference for a specific host. This discovery opens up new avenues for investigating the evolutionary processes at play in chemically-mediated host specialization in the species-rich Cotesia genus.